Regional Modernism - Polish Artistic Culture in the Interwar Period - Krupa, Katarzyna (Sensus Historiae, 2025)
In 2021, a series of exhibitions 4 x modernity opened in Krakow, starting a discussion on modernism, especially its Polish version. With this text, I would like to contribute slightly to the considerations undertaken. In the album accompanying the second of the series of exhibitions, which became the basis for the creation of this article, we find examples from the art of the interwar period. The images are accompanied by texts indicating the polyphonic nature of the phenomenon and its local variations. In the final part of the article, I allow myself to reflect on modernism in general and to briefly signal its impact on the present day.